Pengaruh Penerapan UKBM Terhadap Hasil Belajar Mata Pelajaran Bahasa Jepang Siswa SMA - Ayuna Dewi Ruslika; Ai Sumirah Setiawati (Janaru Saja: Jurnal Program Studi Sastra Jepang (Edisi Elektronik), 2020)
UKBM is a learning process which is arranged in a sequence ranging from an easy to a difficult one. In UKBM system of Japanese language, the students are provided Learning Text-books (BTP) in accordance with basic learning competence (KD). SMA 1 Salatiga is one of the schools that has been using UKBM, that is why it became the object of the research. This study aims to investigate the influence UKBM system towards the students’ learning outcomes in SMA 1 Salatiga. It was conducted by quantitative descriptive method with 73 students as respondents with proportionate stratified random sampling technique. The data collection technique used documentation and questionnaires. The obtained were tested using the Product Moment and produced rhitung is greater than rtabel to a 5% (0.617> 0.227). The result of the calculations is 38%, which means that the application of UKBM in the learning process can influence on the students’ Japanese language learning outcomes by 38%, while the remaining of 62% is determined by other factors. Keywords: The Effects, Application of UKBM, Japanese Language Learning Outcomes.